IMPLEMENTASI ALGORITMA CLASIFICATION ANDREGRESSION TREES (CART) DALAM KLASIFIKASI EKONOMI KELUARGA PADA DESADAGANG KELAMBIR TG.MORAWA - Retno, Eti Yonika Sri (JURIKOM (Jurnal Riset Komputer), 2019)
Family economy is a study of human efforts in meeting their needs through activities carried out by someone who is responsible for the needs and happiness of his life. Data mining is the process of extracting and identifying useful information and related knowledge from various large databases. Daminamining can increase the added value of a database. One of the algorithms in Data Mining is the Clasification And Regression Trees (CART) Algorithm is one method or algorithm of one of the data exploration techniques, namely decision tree technique. CART is fairly simple but is a powerful method. CART aims to get an accurate group of data as a characteristic of a classification. besides that CART is used to describe the relationship between response variables (dependent or non-dependent variables) with one or more predictor variables (independent or independent variables). With the use of weka tools, the results of the implementation process of the Clasification And Regression Trees (CART) algorithm are information or knowledge where the information can be an alternative that can be used by village head office employees in classifying the family economy.